Gambaran Kepatuhan Kunjungan Antenatal Care Pada Ibu Hamil Masa Pandemi Covid-19 di Puskesmas Jatirokeh - Ratna Widhiastuti; Wisnu Widyantoro; Heri Supryanto (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Background: Antenatal care (ANC) regulary on pregnant women expected to be able to early detect and handle complications that often occur in pregnant women. The impact is not the ANC that increase the mortality and morbidity of the mother, didn’ detection of abnormalities pregnancy. How to know the description obedience of pregnant mother in Antenatal Care (ANC) in the area of work Puskesmas Jatirokeh I in September 2021. Methods: This type of research is descriptive quantitative. This research was conducted with cross sectional approach. The technical sampling used purposive sampling with total of respondents there are 40 respondents of pregnancy women in the third trimester in accordance with the inclusion and exclusion criteria. Data analysis using univariate analysis. Result: The research showed that most of the mother pregnant in the third trimester obedient to the examination of the ANC in the working area Puskesmas Kokap I, based on the characteristics of respondents grouped according to age <20 yeras old as many as 26, last aducation the most at the high school or the equivalent as many as 19 and parity the most on a parity multiparous as many as 25. Conclusion: The caracteristics such as age, education, parity, distance, and husband’s support are very influential on the compliance women TM III to perfom ANC regularly.